Effects of visual control training on the shooting performance of elite female basketball players - Oudejans, R. R. D. (International Journal of Sports Science and Coaching, 2012)
In the current study, a method was tested to train visual control in basketball shooting. Using a sender/receiver system, Plato liquid-crystal goggles were wirelessly and manually controlled by the experimenter to manipulate vision of players while they were shooting. During the training the goggles were only open during the final instances of each shot forcing players to use optimal information. In three months, six elite female basketball players, selected on the basis of their shooting style and performance, received 9-15 shot sessions, each consisting of 50 three-point shots with the goggles. Pretest-posttest comparisons revealed that the players who had received the goggle training improved their shooting percentages significantly while two control groups did not. Gradual increases of shooting percentages over training sessions inspired additional confidence in the conclusion that pre-posttest improvements were related to the visual control training. The Plato-goggle system provides a promising tool to be used in sports practice to improve performance.